The Wisdom of Patience in the Story of the Prophet Ayyub As. - Faradiba Hasni Pitaloka; Dody S.Truna (Gunung Djati Conference Series, 2021)
This study aims to discuss the wisdom of patience that is learned from the story of the Prophet Ayyub as. The method used is a qualitative method by applying data analysis. The results and discussion of this study include general views on patience, the story of the Prophet Ayyub as., and the wisdom of patience in the story of the Prophet Ayyub as. As for the conclusion of this study, Allah himself said that the Prophet Ayyub as. is the best servant because he is patient with the test that Allah swt gives. Prophet Ayub as. do not pray to change the situation and always have a good attitude towards Allah SWT.